2020
DOI: 10.21203/rs.3.rs-28869/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing trends of birth weight with maternal age: a cross-sectional study in Xi'an city of Northwestern China

Abstract: Background: Most studies have shown that maternal age is associated with birth weight. However, the specific relationship between each additional year of maternal age and birth weight remains unclear. The study aimed to analyze the specific association between maternal age and birth weight. Methods: Raw data for all live births from 2015 to 2018 were obtained from the Medical Birth Registry of Xi’an, China. A total of 490143 mother-child pairs with full-term singleton live births and the maternal age rangi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The weight of the baby at birth affects birth complications [ 19 , 20 ]. In our study, no difference was found between the two groups in terms of infant birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…The weight of the baby at birth affects birth complications [ 19 , 20 ]. In our study, no difference was found between the two groups in terms of infant birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple gestations have been previously suggested to be associated with RDS in preterm infants, especially in the case of advanced maternal age. [31] In another study performed on singleton infants, [35] parity was associated with respiratory complications and increased risk of developing RDS. The underlying mechanism and the possible association between the surfactant protein deficiency and the parity of the mothers are still unclear, and further studies need to be performed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In the selection of antibody‐negative women as the reference group, maternal age‐matching was used as one of the selection criteria. However, it is well known that neonatal birthweight is associated not only with maternal age 11 but also with parity, pre‐pregnancy body mass index, 12 dietary patterns 13 and maternal anxiety during pregnancy 14 . Therefore, the reference group based on maternal age was not perfect.…”
Section: Discussionmentioning
confidence: 99%